Sulindac exhibits anti-proliferative and anti-invasive effects and enhances the sensitivity to paclitaxel in ovarian cancer - Chen, Shuning; Kong, Weimin; Shen, Xiaochang; Sinha, Nikita; Haag, Jennifer; Deng, Boer; Zhang, Haomeng; John, Catherine; Sun, Wenchuan; Zhou, Chunxiao; Bae-Jump, Victoria L. (Frontiers in Pharmacology, 2025)
ObjectiveChronic inflammation is a key contributor to carcinogenesis, progression, and chemoresistance in ovarian cancer, making inflammatory pathways a logical therapeutic target for the treatment of this disease. Sulindac, a commonly used non-steroidal anti-inflammatory drug, has demonstrated anti-proliferative and anti-invasive effects on several preclinical models of cancer. In this study, we investigated the antitumorigenic effects of sulindac in human ovarian cancer cell lines and a transgenic mouse model of ovarian cancer (KpB).MethodsMTT and colony formation assays were used to evaluate cell proliferation. Cell cycle was detected by Cellometer. ELISA assays were conducted to evaluate the changes of cellular stress, apoptosis and adhesion, while invasion was determined by wound healing assay. Protein expression was examined through Western blotting and immunohistochemistry.ResultsOur results demonstrated that sulindac significantly inhibited cell proliferation, induced cellular stress and apoptosis, caused G1 phase cell cycle arrest, and reduced cell invasion, and suppressed Cox-2 and NF-κB pathways in the MES and OVCAR5 cell lines. Inhibition of cellular stress by N-acetylcysteine partially reversed the anti-proliferative and anti-invasive effects of sulindac. The combination of sulindac and paclitaxel produced synergistic effects in inhibiting cell growth in both paclitaxel sensitive and resistant MES cells. Treatment with sulindac for 4 weeks effectively reduced tumor growth, improved serum levels of inflammatory cytokines and chemokines, and reduced the expression of Cox-2 of ovarian tumors in KpB mice compared with untreated mice.ConclusionsThese findings provide support for the development of clinical trials repurposing sulindac in the treatment of OC, possibly in combination with paclitaxel.